2019
DOI: 10.1007/s40122-019-0130-4
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Migraine Headache on Productivity of Patients According to Migraine Disability Assessment Score: A Cross-Sectional Study

Abstract: IntroductionMigraine, a primary headache disorder, is usually recurrent with moderate to severe intensity. Migraine is the third most common cause of disability under the age of 50. There are various scoring systems for assessing this disability, one of which is MIDAS; the Migraine Disability Assessment Score. The objective of our study was to determine the extent of disability among migraine patients, patterns of prophylaxis, and their healthcare-seeking behaviors.MethodsThis survey was done in 50 migraine pa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
14
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 15 publications
(16 citation statements)
references
References 22 publications
1
14
1
Order By: Relevance
“…Many studies have confirmed the direct effect of gender on the migraine prevalence, severity, intensity of attacks, and related disabilities, as females were found to have a higher degree in all considerations (7). In our study, migraine-related disabilities were also higher in female migraineurs compared with males.…”
Section: Discussionsupporting
confidence: 85%
See 2 more Smart Citations
“…Many studies have confirmed the direct effect of gender on the migraine prevalence, severity, intensity of attacks, and related disabilities, as females were found to have a higher degree in all considerations (7). In our study, migraine-related disabilities were also higher in female migraineurs compared with males.…”
Section: Discussionsupporting
confidence: 85%
“…However, it is the first cause of disability in under 50 years old individuals (19). Migraine-related disabilities include difficulty in doing daily routine activities, a decrease in work performance, and interrupted personal social behaviors (7). In our study, we aimed to clarify the association between migraine disability status, using the MIDAS score, and different personal and social variables.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Secondly, the characteristics of headache were just assessed using HIT-6 and VAS scores in this study. More neuropsychological tests are needed to assess the headache symptom of the migraine, such as the Migraine Disability Assessment Questionnaire (MIDAS) [39] and Visual Light Sensitivity Questionnaire-8 (VLSQ-8) [40]. Furthermore, although we try to diminish the MR scanner noise using earplugs, the tinnitus patients cannot be completely prevented from scanner noise that probably affects the CBF perfusion to varying degree.…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, migraine disability assessment (MIDAS) was used to assess lost days in the past 3 months. It was assessed at the beginning and the end of trial [ 30 ].…”
Section: Methodsmentioning
confidence: 99%